BTDAzo: A Photoswitchable TRPC5 Channel Activator. Issue 36 (27th July 2022) - Müller, Markus; Niemeyer, Konstantin; Urban, Nicole; Ojha, Navin K.; Zufall, Frank; Leinders‐Zufall, Trese; Schaefer, Michael; Thorn‐Seshold, Oliver
Abstract: Photoswitchable reagents can be powerful tools for high‐precision biological control. TRPC5 is a Ca 2+ ‐permeable cation channel with distinct tissue‐specific roles, from synaptic function to hormone regulation. Reagents giving spatiotemporally‐resolved control over TRPC5 activity may be key to understanding and harnessing its biology. Here we develop the first photoswitchable TRPC5‐modulator, BTDAzo, to address this goal. BTDAzo can photocontrol TRPC5 currents in cell culture, as well as controlling endogenous TRPC5‐based neuronal Ca 2+ responses in mouse brain slices. BTDAzo s are also the first reported azo‐benzothiadiazines, an accessible and conveniently derivatised azoheteroarene with strong two‐colour photoswitching. BTDAzo ′s ability to control TRPC5 across relevant channel biology settings makes it suitable for a range of dynamically reversible photoswitching studies in TRP channel biology, with the aim to decipher the various biological roles of this centrally important ion channel. Abstract : The TRPs (Transient Receptor Potentials) are important sensory ion channels with roles in perception including of heat, cold, and electrophiles, as well as in signaling and mineralostasis. Here the first photopharmaceutical TRPC5 ligand, BTDAzo, is developed, which achieves outstanding photoswitchability of TRPC5 currents in physiological models including brain slice, without crosstalk to the related TRPC4 channel.